Focus on P2X7R in microglia: its mechanism of action and therapeutic prospects in various neuropathic pain models - Zhang, Kai; Ran, Rui; Zhang, Cheng-Jun; Wang, Linna; Zhang, Hai-Hong (Frontiers in Pharmacology, 2025)
Neuropathic pain (NP) is a common symptom of many diseases and is caused by direct or indirect damage to the nervous system. Tricyclic antidepressants and serotonin-norepinephrine reuptake inhibitors are typical drugs used in clinical practice to suppress pain. However, these drugs have drawbacks, including a short duration of action, a limited analgesic effect, and possible dependence and side effects. Therefore, developing more effective NP treatment strategies has become a priority in medical research and has attracted much research attention. P2X7 receptor (P2X7R) is a non-selective cation channel activated by adenosine triphosphate and is mainly expressed in microglia in the central nervous system. Microglial P2X7R plays an important role in pain regulation, suggesting that it could be a potential target for drug development. This review comprehensively and objectively discussed the latest research progress of P2X7R, including its structural characteristics, functional properties, relationship with microglial activation and polarization, mechanism of action, and potential therapeutic strategies in multiple NP models. This study aimed to provide in-depth insights into the association between P2X7R and NP and explore the mechanism of action of P2X7R in the pathological process of NP and the translational potential and clinical application prospects of P2X7R antagonists in pain treatment, providing a scientific basis for the precise treatment of NP.